Smart Prenatal Care Systems and the Future of Obstetric Healthcare - Lucas Mendess Ribeiro; Camila Ferreira Santos (Generasi Sains Indonesia, 2026)
This study examines the implementation of smart prenatal care systems in maternal healthcare services in Amazonas, Brazil, with particular attention to tele-obstetrics, digital prenatal monitoring, and healthcare accessibility in geographically isolated communities. The research aims to analyze how digital healthcare innovation contributes to improving obstetric services while simultaneously identifying structural and institutional barriers affecting implementation effectiveness. A qualitative case study approach was employed through semi-structured interviews, field observations, and document analysis involving healthcare professionals, pregnant women, healthcare administrators, and policymakers in Manaus and surrounding riverine communities. The findings indicate that smart prenatal care systems significantly improved communication between healthcare providers and pregnant women, strengthened early detection of pregnancy risks, and enhanced healthcare coordination in remote regions. However, infrastructural inequality, unstable internet connectivity, limited digital literacy, and shortages of healthcare personnel remained major constraints affecting service effectiveness. The study contributes to discussions on digital health governance, healthcare equity, and maternal healthcare transformation in developing regions while emphasizing the importance of inclusive infrastructural and institutional development for sustainable tele-obstetric implementation.